PROSPEK PEMASARAN BENIH IKAN MAS (CYPRINUS CARPIO L) MELALUI PENGEMBANGAN AGRIBISNIS PERIKANAN DI KABUPATEN SOPPENG. - Yuliana Yuliana (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
This research aimed to find out the prospect of goldfish seed marketing based on the market demand and opportunity in Soppeng regency. This research was a descriptive study. The primary were gathered from the farmers and the agents of goldfish seed marketing from the farmers and the agents were obtained from the department of Fishery and office and BBIS. The data werw collected through observation and interview. Then they were analyzed using SWOT analysis. The results showed that based on SWOT analysis there are internal and external factor indicating that the expansion of market segment of goldfish seed in Soppeng Regency has a good prospect .